KEMAMPUAN MEMAHAMI KOHESI DAN KOHERENSI PARAGRAF PADA KARANGAN NARASI MAHASISWA SEMESTER I KEBIDANAN POLITEKNIK KESEHATAN TERNATE - Samsu Somadayo; Eko Purnomo (PEDAGOGIK, 2021)
The purpose of this study was to determine the first semester students’ ability to understand the cohesion and coherence in narrative paragraph and to describe the results of the analyzing students’ ability to understand cohesion and coherence in narrative paragraph. This is aqualitative research by applying the qualitative descriptive method in analyzing data, the data received can be interpreted by examining the data, checking the validity of the data, and describing the first semester students of Ternate Health Polytechnics’ writing narrative essays. The results of this study indicate that the first semester students of the Ternate Health Polytechnic do not yet understand the cohesion and coherence between paragraphs in narrative essays. As a result of the lack of student understanding of the cohesion and coherence between the paragraphs, the student has not been able to apply it in their writing discourse it is always not cohesive and incoherent.